Stroke and immunotherapy: Potential mechanisms and its implications as immune‐therapeutics. (26th May 2021) - Chavda, Vishal; Madhwani, Kajal; Chaurasia, Bipin
Abstract: Ischemia or brain injuries are mostly associated with emergency admissions and huge mortality rates. Stroke is a fatal cerebrovascular malady and second top root of disability and death in both developing and developed countries with a projected rise of 24.9% (from 2010) by 2030. It's the most frequent cause of morbidities and systemic permanent morbidities due to its multi‐organ systemic pathology. Brain edema or active immune response cause disturbed or abnormal systemic affects causing inflammatory damage leading to secondary infection and secondary immune response which leads to activation like pneumonia or urine tract infections. There are a variety of post stroke treatments available which claims their usefulness in reducing or inhibiting post stroke and recurrent stroke damage followed by heavy inflammatory actions. Stroke does change the quality of life and also ensures daily chronic rapid neurodegeneration and cognitive decline. The only approved therapies for stroke are alteplase and thrombectomy which is associated with adverse outcomes and are not a total cure for ischemic stroke. Stroke and immune response are reciprocal to the pathology and time of event and it progresses till untreated. The immune reaction during ischemia opens new doors for advanced targeted therapeutics. Nowadays stem cell therapy has shown better results in stroke‐prone individuals. Few monoclonal antibodies like natalizumab have shown great impact on pre‐clinical and clinical stroke trial studies. In this current review, we have explored an immunology of stroke, current therapeutic scenario and future potential targets as immunotherapeutic agents in stroke therapeutics. Abstract : Schematic illustration describes immunotherapy as a promising adjuvant therapy to improve stroke associated impairments.